Interdisciplinary Surgical Treatments and Long-Term Outcomes of Lumbar Spinal Tumors With Retroperitoneal Involvements: A Retrospective Case Series Study - He, Shaohui; Bi, Yifeng; Ye, Chen; Peng, Dongyu; Xiao, Jianru; Wei, Haifeng (Frontiers in Oncology, 2021)
Purpose Surgical treatments are technically challenging for lumbar spinal tumor (LST) with extensive retroperitoneal involvements. Our study aimed to report the experience and outcomes concerning interdisciplinary surgical collaborations in managing such LSTs. Patients and Methods Nine patients underwent interdisciplinary surgical treatments which were performed by specialists, namely, spinal, vascular, and urinary surgeries. Data on clinical characteristics were collected, and the Visual Analogue Scale (VAS) and the Japanese Orthopaedic Association Score (JOAS) were used in the evaluation before and after surgery. The postoperative complications and the long-term outcomes were reported as well. Results The interdisciplinary work included double J catheter indwelling (n = 9), nephrostomy (n = 5), replacement of the common iliac vein (n = 2), abdominal aorta repair (n = 3), and vital vessel repair (n = 8). The early-stage complications included complaints of moderate low back pain and slight implant shift (n = 1, 11.1%) and tardive ureterodialysis (n = 1, 11.1%). The 3- and 5-year disease-free survival rates were 76.2 ± 14.8 and 50.8 ± 23.0%, respectively, during the mean follow-up of 34.6 ± 17.9 months (range, 9.5–68.7). Besides this, more blood loss was associated with recurrent and metastatic tumor status (p = 0.043) and surgery time >5 h (p = 0.023). Remarkable pain relief and favorable quality of life were achieved based on the postoperative VAS (3.3 ± 0.9, p < 0.001) and JOAS (16.6 ± 0.5, p < 0.001). Conclusions The treatments of LSTs with wide-range retroperitoneal involvements require interdisciplinary surgical collaborations to lower the risks and improve the long-term outcomes. High-quality prospective cohort studies with large samples are warranted to establish general surgical protocols in managing LSTs with extensive retroperitoneal involvements.